Sistem Pendukung Keputusan dalam Identifikasi Motif Songket Silungkang Menggunakan Metode AHP - Humairoh, Putri; Nurcahyo, Gunadi Widi (Jurnal Sistim Informasi dan Teknologi, 2021)
Songket Silungkang is a traditional weaving product made with special tools and is the creation of weavers from the Silungkang area. Songket has various types of motifs that are currently popular in Indonesia. So that it becomes a consideration for songket enthusiasts to get information about the songket motif. In this case, a proper analysis is needed to speed up the identification process in determining the Silungkang songket motif. Therefore we need a model that can describe all computerized systems that support the decision-making process. The decision support system using the Analytical Hierarchy Process method assesses each motive with the criteria and changes in the weight value. The criteria used in identifying Silungkang songket motifs are the type of material, the shape of the motif and the color of the motif. This study produces a matrix of yield weight, with the highest value of 90.0%. So that from the final results of the calculation, it can be identified that the most popular songket Silungkang motif at the INJ Songket Store is the pucuak rabuang motif. This is useful for facilitating decision making related to the identification of Silungkang songket motive in the future.